2010
DOI: 10.1007/s00586-010-1295-z
|View full text |Cite
|
Sign up to set email alerts
|

Posterior approach to ventrally located spinal meningiomas

Abstract: For the resection of anteriorly located meningiomas, various approaches have been used. Posterior approach is less invasive and demanding; however, it has been associated with increased risk of spinal cord injury. We evaluated ten consecutive patients that underwent surgery for spinal meningiomas. All patients were preoperative assessed by neurological examination, computed tomography and magnetic resonance imaging. All tumors were ventrally located and removed via a posterior approach. Transcranial motor-evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In most cases, spinal cord meningiomas are WHO grade I tumors, and gross total removal is possible with a conventional posterior approach utilizing these anatomical features [1,2,4,5,[15][16][17][18]. Simpson grade I removal (macroscopically complete removal of a tumor and its visible extensions, with excision of its dural attachment and of any abnormal bone) [19] is considered the most effective way to avoid recurrence [5].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, spinal cord meningiomas are WHO grade I tumors, and gross total removal is possible with a conventional posterior approach utilizing these anatomical features [1,2,4,5,[15][16][17][18]. Simpson grade I removal (macroscopically complete removal of a tumor and its visible extensions, with excision of its dural attachment and of any abnormal bone) [19] is considered the most effective way to avoid recurrence [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, they opined that if the lesion is in the cervical or upper-lumbar spine, early mobilisation might be hazardous if the spinal column has not been stabilised. Fear of destabilising the spine should not compromise the exposure required to safely remove these tumours 23,24 . The detection of calcification within a mass is important to estimate the difficulty of resection or post-operative prognosis as well as to narrow the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have reported using a direct posterior approach for treatment of ventral thoracic pathology, 31 most authors recommend avoiding it, as this technique risks damage to the spinal cord. 2,18,25,29,30 The costotransversectomy approach provides access to ipsilateral ventrolateral pathology extending to, but not across, the midline.…”
Section: Technical Advantagesmentioning
confidence: 99%